Entorhinal cortex and parahippocampus volume reductions impact olfactory decline in aged subjects. Issue 5 (26th March 2021) - Iizuka, Natsuko; Masaoka, Yuri; Kubota, Satomi; Sugiyama, Haruko; Yoshida, Masaki; Yoshikawa, Akira; Koiwa, Nobuyoshi; Honma, Motoyasu; Watanabe, Keiko; Kamijo, Shotaro; Kamimura, Sawa; Ida, Masahiro; et al.
Abstract: Introduction: Pathological abnormalities first appear in the medial temporal regions including entorhinal cortex and parahippocampus in patients with Alzheimer's disease. Previous studies showed that olfactory decline in elderly subjects was associated with volume reductions in the left hippocampus and left parahippocampus without cognitive impairment. The aim of this study is to investigate the link between olfaction and volume reductions in the medial temporal regions including the parahippocampus, entorhinal cortex, and hippocampal subfields. Method: 27 elderly subjects and 27 young controls were measured olfaction acuity, cognitive function, and structural magnetic resonance imaging. Image processing and gray matter volumetric segmentation were performed with FreeSurfer. Volume data were analyzed with SPSS Statistics software. Results: Interesting results of this study were that volume reduction in the entorhinal cortex was not directly linked with declining olfactory ability. Volume reduction in the left entorhinal cortex was correlated with volume reduction in the left parahippocampus and dentate gyrus. However, left parahippocampus volume reduction had the greatest impact on olfactory decline, and the entorhinal cortex and dentate gyrus might additionally contribute to olfactory decline. Conclusion: Our results indicate that olfactory decline may be directly reflected in the medial temporal regions as reduced parahippocampus volumes, rather than as morphological changes in the entorhinal cortex and hippocampus. The parahippocampus may play an important role in the association between memory retrieval and olfactory identification. Abstract : Left: Visualization of brain segmentation in a single subject with FreeSurfer. The entorhinal cortex (ENT) is indicated in red, and the parahippocampus (para‐HI) is indicated in green. Right: Visualization of hippocampal subfield segmentation in a single subject with each subfield represented by a different color.